Sunrise Point - Carr, Robyn (Don Mills, Ont. : MIRA Books, 2012)
Former marine Tom Cavanaugh has come home to Virgin River, ready to take over his family's apple orchard and settle down. He knows just what the perfect woman will be like: sweet, decent, maybe a little naive. The "marrying" kind. Nothing like Nora Crane. So why can't he keep his eyes off the striking single mother?
Keywords: Man-woman relationships -- Fiction; Single parents -- Fiction; Love stories